Reframing Human Capital: The Strategic Role of Digital Literacy in 21st Century Workforce Development - Adekoya, Oluwatoyosi Deborah (Electronic Journal of Business and Management, 2025)
The workplace in the 21st century is changing at a breakneck pace, all thanks to digital technologies that are reshaping the skills we need across various industries. In this dynamic environment, digital literacy has become a crucial part of our human capital, playing a significant role in employability, fostering innovation within organizations and bolstering national economic resilience. This paper delves into the strategic importance of digital literacy as it fits into the larger picture of human capital development and workforce growth. By drawing on a mix of theories including human capital theory, digital capital theory and socio-technical systems theory, it provides a thoughtful analysis that positions digital literacy as a vital factor for economic participation and adaptability in knowledge-driven economies. The research highlights how essential digital skills are not just as technical know-how but also as gateways to lifelong learning, social inclusion, and active digital citizenship. It also investigates the structural challenges that hinder digital inclusion in developing regions, such as gaps in infrastructure, educational shortcomings and institutional resistance to change. The paper wraps up by stressing the need to weave digital literacy into national education policies, workforce initiatives and development plans to create resilient and inclusive economies. Without targeted investments in digital human capital, countries risk widening the gap of inequality and jeopardizing their competitiveness on the global stage.